Immunological profile of erythema nodosum and their relationship of C-reactive protein level and erythrocyte sedimentation rate: A retrospective analysis of 61 patients: Immunological profile of erythema nodosum - Cao, Chunyu; Chen, Lihua; Li, Shu; Wang, Yishan; Yuan, Lili (Cellular and Molecular Biology, 2022)
This experiment was carried out to investigate changes in lymphocyte subpopulation, immunoglobulins (Igs), and complements, and also to explore the relationship between these immune indices and C-reactive protein and erythrocyte sedimentation rate in 61 patients with erythema nodosum. For this aim, a 4-year, retrospective study contained 61 patients with erythema nodosum, and 61 healthy control subjects were included from the out-patient clinic. The subpopulation of the T, B and natural killer lymphocytes and levels of IgA, IgG, IgM, complement C3, complement C4, C-reactive protein, and erythrocyte sedimentation rate from peripheral blood of them were detected. A correlation analysis was done between lymphocyte subpopulation, levels of IgA, IgG, and IgM, complement C3, complement C4 and C-reactive protein level and erythrocyte sedimentation rate in the patient group. Results showed that the percentage of CD4+ cells, CD4+/CD8+ ratio, the level of C-reactive protein and the erythrocyte sedimentation rate in the patients were higher than in controls (P<0.05). While the percentage of CD8+ cells and the serum levels of complement C3 were lower than in controls (P<0.05). There were no differences in the percentages of CD3+, B and natural killer cells and the serum levels of IgA, IgG and IgM, and complement C4 between the patients and the controls (P>0.05). IgM level was positively correlated with C-reactive protein (P<0.05) but did not correlate with an erythrocyte sedimentation rate (P>0.05). There was no correlation between lymphocyte subpopulation, levels of IgA, IgG, complement C3, complement C4 and C-reactive protein level and erythrocyte sedimentation rate (P>0.05). In conclusion, there was dysregulation of both cellular immunity and humoral immunity in patients with erythema nodosum. IgM level has a positive correlation with C-reactive protein.